Business cycle narratives - Vegard Høghaug Larsen; Leif Anders Thorsrud (Norges Bank, 2018)
This article quantifies the epidemiology of media narratives relevant to business cycles in the US, Japan, and Europe (euro area). We do so by first constructing daily business cycle indexes computed on the basis of the news topics the media writes about. At a broad level, the most in fluential news narratives are shown to be associated with general macroeconomic developments, finance, and (geo-)politics. However, a large set of narratives contributes to our index estimates across time, especially in times of expansion. In times of trouble, narratives associated with economic fl uctuations become more sparse. Likewise, we show that narratives do go viral, but mostly so when growth is low. While narratives interact in complicated ways, we document that some are clearly associated with economic fundamentals. Other narratives, on the other hand, show no such relationship, and are likely better explained by classical work capturing the market's animal spirits
hdl:11250/2500929
Keywords: 330; business cycles; narratives; dynamic factor model; latent dirichlet allocation; C55; E32; E71; N10